2016
DOI: 10.1186/s12889-016-3197-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sun protection behaviours and sunburn among Australian adolescents

Abstract: BackgroundExcessive sun exposure and sunburn increase individuals’ risk of skin cancer. It is especially important to prevent sunburn in childhood due to the higher relative risk of skin cancer across the life span compared to risk associated with sunburn episodes experienced later in life. This study examined demographic and attitudinal factors associated with engagement in a range of sun protection behaviours (wearing a hat, wearing protective clothing, staying in the shade, and staying indoors during the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
(46 reference statements)
2
30
2
1
Order By: Relevance
“…For patients who are non‐adherent, the design of effective behaviour change interventions is required and needs to be informed by knowledge of psychological factors associated with poor protection. In the general population, photoprotection behaviour has been associated with beliefs about photoprotection [(e.g., personal vulnerability, benefits of protection, barriers (Bränström et al ., ; Pettigrew et al ., )], self‐efficacy (Good & Abraham, ), intention, and automaticity (behaviours that are enacted with little conscious awareness ) (Allom, Mullan, & Sebastian, ). The importance of treatment beliefs, and to a lesser extent illness perceptions, in explaining adherence has been reported across other chronic conditions (e.g., Broadbent, Donkin, & Stroh, ; Horne et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For patients who are non‐adherent, the design of effective behaviour change interventions is required and needs to be informed by knowledge of psychological factors associated with poor protection. In the general population, photoprotection behaviour has been associated with beliefs about photoprotection [(e.g., personal vulnerability, benefits of protection, barriers (Bränström et al ., ; Pettigrew et al ., )], self‐efficacy (Good & Abraham, ), intention, and automaticity (behaviours that are enacted with little conscious awareness ) (Allom, Mullan, & Sebastian, ). The importance of treatment beliefs, and to a lesser extent illness perceptions, in explaining adherence has been reported across other chronic conditions (e.g., Broadbent, Donkin, & Stroh, ; Horne et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Objective data relating to sun protection behaviours (detailed below) were captured over a period of 20 school days across February/March 2019. In an effort to overcome the noted limitations of previous research that has typically relied on self-reported sun-protection behaviours [13][14][15], behavioural data in the form of shade and hat use (via schoolyard photographs), sunscreen use (via the provision of sunscreen bottles), and UVR exposure (via the application of polysulfone badges) were captured objectively. Both schools had two cameras located within school grounds, one in a sunny position and one in a shaded area.…”
Section: Objective Data Collectionmentioning
confidence: 99%
“…It has been noted that a limitation of previous research has been the inability to separate out the effects of the UVI component of interventions testing the effectiveness of other dissemination methods, such as television broadcasts, websites, and apps [35]. Further, the present study combined self-report and observational methods of data collection to overcome the reliance in previous research on self-reported enactment of sun protection behaviours among adolescents [13][14][15].…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the tennis court officials in UVR protective uniforms provides positive sun-safe role models for adults and adolescents alike. Their visual presence provides a latent but persistent advertisement, modeling sun-safe behaviors while engaged in physical activity (3,4,12,20,45,56,60). An analogy is the relatively recent change in the iconic and very visible Australian surf lifesaver uniforms to include broad brim "bucket" hats, long-sleeved shirts and visible sunscreen (45), particularly as they often appear in local advertising campaigns, which is an important aspect of modeling and endorsing sun-safe behaviors (8,12,19,20,45,56,60).…”
Section: Calculated Solar Ultraviolet Exposurementioning
confidence: 99%